2018
DOI: 10.11609/jott.3874.10.11.12602-12606
|View full text |Cite
|
Sign up to set email alerts
|

New nymphalid butterfly records from Jammu & Kashmir, India

Abstract: The present communication deals with the new nymphalid butterfly records from the state of Jammu and Kashmir. The sightings are based on the butterfly surveys conducted in different ecosystems of Jammu region in a span of two years. The paper calls for more organized and intensive butterfly surveys to understand their status, distribution and population dynamics in and around Jammu.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…The same study reports the confirmed use of Xylosma longifolia Clos by this species as a larval host plant in Dehradun (Western Himalaya). The adults are observed to feed on flower nectar (Polygonum hydropiper L. -Water Pepper Plant and Lantana camara L. -Wild Sage, being two such plants) and animal excretions (bird droppings, cow urine and dung), and also involve in mud-puddling (Naro & Sondhi, 2014;Sondhi & Kunte, 2018;Sharma & Sharma, 2018;Kumar, Kushwaha & Namdev, 2020). They have been found to opportunistically feed on flower nectar in the forest canopy during some migrations in the Tam Dao mountains in Vietnam (Spitzer et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The same study reports the confirmed use of Xylosma longifolia Clos by this species as a larval host plant in Dehradun (Western Himalaya). The adults are observed to feed on flower nectar (Polygonum hydropiper L. -Water Pepper Plant and Lantana camara L. -Wild Sage, being two such plants) and animal excretions (bird droppings, cow urine and dung), and also involve in mud-puddling (Naro & Sondhi, 2014;Sondhi & Kunte, 2018;Sharma & Sharma, 2018;Kumar, Kushwaha & Namdev, 2020). They have been found to opportunistically feed on flower nectar in the forest canopy during some migrations in the Tam Dao mountains in Vietnam (Spitzer et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…2): India (Bingham, 1905), containing the most northern and western distribution of the species as well as the subspecies; Nepal (Varshney, 1994); Bhutan ; Bangladesh (Larsen, 2004); Myanmar (Bingham, 1905); Thailand (Varshney, 1994), containing the southernmost distribution of the subspecies; Cambodia (Savela, nd); Laos (No record, but most likely); Vietnam (Spitzer et al, 1993);and China (D'Abrera, 1940), including the special autonomous region Hong Kong (Bascombe, Johnston & Bascombe, 1999) -containing the easternmost distribution of the subspecies. In India, they are found within 14 states and one union territory across the Himalayan range, its foothills, Eastern Ghats and near the Eastern coast -Jammu & Kashmir (Sharma & Sharma, 2018), which is the northernmost and westernmost distribution in their range; Himachal Pradesh ; Chandigarh (Soman, 2015); Uttarakhand (Bingham, 1905); Uttar Pradesh (Kumar, Kushwaha & Namdev, 2020); Sikkim (Wynter-Blyth, 1957); West Bengal (Bingham, 1905); Arunachal Pradesh (Kunte, 2007), their easternmost distribution in India; Assam (Bingham, 1905); Nagaland (Tytler, 1911); Mizoram (Bhakare, 2009); Tripura (Zothansangi, 2015); Odisha (Wynter-Blyth, 1957); Chattisgarh (Naidu, 2018); and Andhra Pradesh (Saragada, 2020), which is their southernmost distribution within India. Records of this subspecies have increased considerably over the past half-a-decade, with many new sightings to the west of their previously known range in North-West India.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The butterflies inhabiting these habitats show a variety of distributional patterns in different elevational bands. The region has quite recently emerged as a potential butterfly hotspot contributing several new species to the lepidopteran fauna of Jammu and Kashmir (Sharma & Sharma 2018a, 2018b.…”
mentioning
confidence: 99%
“…The Zanskar range of Great Himalayas separates Kishtwar from Ladakh in north-east. While a good account of butterfly fauna is available for Kashmir (Home 1938;Mani & Singh 1962;Das et al 1964;Das & Verma 1965;Dar et al 2002;Khan et al 2011;Qureshi et al 2014;Qureshi 2020), Jammu region is data deficient, except for a few recent reports by Sharma & Sharma (2017a, 2017b, 2018a, 2018b, Sharma et al (2019) and Sheikh & Parray (2019).…”
mentioning
confidence: 99%